Polaritonic molecular clock for all-optical ultrafast imaging of wavepacket dynamics without probe pulses - R. E. F. Silva; Javier del Pino; Francisco J. García-Vidal; Johannes Feist (Nature Communications, 2020)
Pump-probe method is commonly used for studying ultrafast molecular dynamics. Here, the authors discuss alternative approach of using time-dependent ultrafast light emission from excited molecules coupled to a plasmonic nanocavity instead of using probe pulse.